EFEKTIVITAS COOPERATIVE LEARNING TIPE PAIR CHEK PADA MATERI SISTEM PENCERNAAN - Ospa Pea Yuanita Meishanti; Iin Baroroh Ma'arif (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2017)
Abstract In studying the concept of biology is not only enough to memorize it but it is necessary to have a direct learning experience by linking between the subject matter obtained with real life everyday. Lecturers no longer act as a learning resource that always convey materials to the students and make presentations, but acts as a mentor and facilitate for students willing and able to learn. Students are not regarded as a learning object that can be restricted and organized according to the lecturers' wishes, but students are placed as subjects who can learn according to their talents, interests, and abilities. Lecturers are required to be creative and innovative in developing also apply learning tools in accordance with the learning style and characteristics of the students. Where lecturers should be able to determine the appropriate learning model in teaching, so that there is an active interaction between students, lecturers with students, and students with the environment. Learning Cooperative learning can make it easier for students to learn. Students will describe the digestive system, so that the learning experience that students get through the activities during the learning will improve students' understanding. The method used in the research using experimental method with the design of One Group Pratest-Postest Design. From the analysis of the development of pretest and posttest values, in this study showed an increased posttest score, student response analysis of the Cooperative Learning Type Pair Chekk show students are motivated to follow the learning. Keywords: Effectiveness, cooperative learning, Pair Check model